2019
DOI: 10.1016/j.marpolbul.2017.12.031
|View full text |Cite|
|
Sign up to set email alerts
|

Non-indigenous macrozoobenthic species on hard substrata of selected harbours in the Adriatic Sea

Abstract: The intense shipping traffic characterising the Adriatic Sea favours the spread of marine organisms. Yet, a study of 12 Adriatic ports (4 on the western side and 8 on the eastern side of the basin) found that non-indigenous species (NIS) accounted for only 4% of the benthic communities settled on hard substrates. The cirripeds Amphibalanus amphitrite and Balanus trigonus, found in 8 harbours, were the most common invaders followed by Amphibalanus eburneus, the ascidian Styela plicata, and the bivalve Magallana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 69 publications
4
19
0
Order By: Relevance
“…Our study detected wild populations of M. gigas along the entire west coast of Istria, which is neighbouring area of the above mentioned regions and further extension of the Eastern Adriatic southwards. Confirming the previous study by SPAGNOLO et al (2019) which assessed non-native macrozoobenthic species in twelve ports throughout the entire Adriatic basin during 2014, our study did also not record any M. gigas specimens in the CE and SE Adriatic, except at one location that was not included in their study (i.e., Biograd na Moru). SPAGNOLO et al (2019) did not record the species neither in ports in Montenegro nor Albania.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Our study detected wild populations of M. gigas along the entire west coast of Istria, which is neighbouring area of the above mentioned regions and further extension of the Eastern Adriatic southwards. Confirming the previous study by SPAGNOLO et al (2019) which assessed non-native macrozoobenthic species in twelve ports throughout the entire Adriatic basin during 2014, our study did also not record any M. gigas specimens in the CE and SE Adriatic, except at one location that was not included in their study (i.e., Biograd na Moru). SPAGNOLO et al (2019) did not record the species neither in ports in Montenegro nor Albania.…”
Section: Resultssupporting
confidence: 90%
“…Confirming the previous study by SPAGNOLO et al (2019) which assessed non-native macrozoobenthic species in twelve ports throughout the entire Adriatic basin during 2014, our study did also not record any M. gigas specimens in the CE and SE Adriatic, except at one location that was not included in their study (i.e., Biograd na Moru). SPAGNOLO et al (2019) did not record the species neither in ports in Montenegro nor Albania. However, the authors reported the presence of the species in all Italian and Slovenian ports surveyed, as well as in the Port of Pula in Croatia.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Numerous specimens of the species were also observed in the same area attached to hard substrata in the 2018 surveys (February, May, August). This is first finding from Montenegrin waters, although the species was expected (Karachle et al, 2017) since the species has been long established in the Adriatic Sea: Italy: (Heller, 1877); Croatia, Slovenia and Albania (Spagnolo et al, 2018).…”
Section: Slavica Petovićmentioning
confidence: 71%